A Review Study On Properties Of Praval According To Various Textbooks Of Ayurveda And Its Effects On Prana-Vaha Srotas With Special Reference To Its Bhutaghna Property. - Khatana, Anil; Kalra, Samita; Mishra, Yogiraj (International Research Journal of Ayurveda & Yoga, 2021)
Praval (coral) i Virya, Vipaka, Prabav etc. Therefore, the effect of Praval Bhasma is expected on the microbes, whics used in Ayurveda for medicinal purpose in the form of Bhasma And Pishti. Both of these preparations play an important role in subsiding diseases like kshay, kasa, raktpita, timir etc. Prawal have properties like- Deepan, Pachan, Vishad, Vish Shaman and Bhootshaman etc.2 These properties must potentially play significant role in the therapeutical properties prawal shows in above mentioned diseases, because every medicine performs there functions according to their Ras, Gun,h could be the effect of the Bhootshaman property (antibacterial). Invitro study on the effects of prawal preparations on microorganism can be done in this direction too. Kaasa, Shwaas, Kshaya etc. diseases which are Prana vaha srotodushti janya roga, in which Pravala Bhasam and Pravala Pishti are being successfully used from a long time due to its effectiveness. Along with the other causes, Kaas and Kshaya are one of the symptoms of some acute and chronic infections, which alters the physiology of Pranavaha Srotasa and cause Pranavaha Srotodushti. These infectious can be considered as aagantuj rog/bhuta-bhishang etc. While the prawal is being used in both infectious and non-infectious kaas and kshaya. Thus, the properties of Prawal collected from various Samhita and manuscripts of Ayurveda could explain the Karmukta of Prawal on Prana-vaha srotodushti janya roga along with the role of its bhutaghna property.